Assessment of early symptoms of surgical menopause in patients with borderline ovarian tumors - A. Yu. Vlasina; A. G. Solopova; A. E. Ivanov; I. M. Zhalyalova (IRBIS LLC, 2020)
Aim: to make a comparative evaluation of women with borderline ovarian tumors (BOTs) and surgical menopause (early symptoms) and explore their level of anxiety and depression depending on the age and volume of surgery.Materials and methods. The prospective comparative study included 117 patients, aged 44.3 ± 6.5 years, after surgical treatment of BOTs: 62 women at reproductive age with surgical menopause after radical treatment (group IА), 24 women at reproductive age after organ-preserving surgery (group IВ), 31 women at perimenopausal age after radical treatment (group II). The severity of menopausal syndrome (modified menopausal Kupperman-Uvarova index), anxiety and depression (Hospital Anxiety and Depression Scale, HADS) were determined 29-59 (36.4 ± 5.6) days after surgery.Results. Early symptoms of surgical menopause are found in 98.3 % of patients with BOTs. Reproductive age patients after radical surgery (group IA) had moderate neurovegetative (21.7 ± 4.0 points), mild metabolic (5.8 ± 1.8 points), and moderate psychoemotional disorders (8.9 ± 1.4 points). Young women who underwent organ-saving operations with preservation of at least one ovary (group IB), had normal range the indicators of neurovegetative disorders (8.2 ± 3.1 points), metabolic and psychoemotional disorders were regarded as moderate (2.6 ± 1.6 and 5.9 ± 2.3 points, respectively). Disorders due to surgical menopause (early symptoms) at perimenopausal age females (group II) corresponded to a mild degree: neurovegetative - 15.3 ± 2.7 points; metabolic - 6.0 ± 2.2 points; psychoemotional - 5.7 ± 1.5 points. Our data indicate that patients of group IA had moderate surgical menopause (early symptoms) - 36.4 ± 5.4 points, while in groups IB and II the total values were 16.8 ± 5.4 and 27.0 ± 4.3 points, which corresponds to mild severity. Patients with BOTs (one month after antitumor therapy) had early symptoms of surgical menopause (postovariectomy syndrome). The most typical clinical picture was observed among young women after removal of both ovaries.Conclusion. Surgical menopause affects by somatic and psychological health negatively. This leads to a significant decrease in the quality of life and an increase in the level of disability among patients with gynecological cancer. Therefore, even at the planning treatment, it is necessary to include pre-rehabilitation measures to minimize the negative consequences of cancer therapy.